Analisis Rasio Sebagai Dasar Pengukuran Kinerja Keuangan Pada Koperasi Simpan Pinjam Syariah BMT UGT Sidogiri - Salim, Helmi Agus; Nurbailah, Amiroh (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2018)
Saving and loan cooperative Syariah BMT UGT Sidogiri is one of financial institutions in which its activity is to collect fund from the members and distribute it through the mechanism of the islamic financial services business. It is from and for cooperative members, or even the candidate ones. With more and more competitors and the uncertain of the economic condition of indonesia affects unstable condition in its financial sector. To know that financial condition, needed appraisal toward Saving and loan cooperative Syariah BMT UGT Sidogiri financial performance by applying analysis against financial performance through the financial ratios.This observation using calculation concern with the data in the form of financial report. Meanwhile, the analysis tool which is used in this observation is financial ratios which covers liquidity ratio, solvency ratio, and profitability ratio.Overall from 2014-2017 analysis which is done produces good enough ratio except cash ratio analysis. That gains the smallest ratios, because in analyzing it conceptually does not invoive credit accounts, where in this Saving and loan cooperative Syariah BMT UGT Sidogiri the greatest wealth is got from credit accounts in accordance with the type of cooperative business namely Saving and loan cooperative.